Power system protection - Anderson, P. M. (Paul M.), 1926- (New York : McGraw-Hill : IEEE Press, 1999)
"In a world of huge, interconnected networks that can be completely blacked out by disturbances, Power System Protection offers an improved understanding of the requirements necessary for prompt and accurate corrective action." "P. M. Anderson, a noted expert on power systems, presents an analytical and technical approach to power system protection. His discussion shows how abnormal system behavior can be detected before damage occurs, and points to effective control action to limit system outages." "Power System Protection is written for practicing engineers and advanced graduate-level student engineers, who need a comprehensive resource on the principles of power system behavior and methods of system analysis."--Jacket.
pt. I. Protective Devices and Controls -- Ch. 1. Introduction -- Ch. 2. Protection Measurements and Controls -- Ch. 3. Protective Device Characteristics -- Ch. 4. Relay Logic -- Ch. 5. System Characteristics -- pt. II. Protection Concepts -- Ch. 6. Fault Protection of Radial Lines -- Ch. 7. Introduction to Transmission Protection -- Ch. 8. Complex Loci in the Z and Y Planes -- Ch. 9. Impedance at the Relay -- Ch. 10. Admittance at the Relay -- pt. III. Transmission Protection -- Ch. 11. Analysis of Distance Protection -- Ch. 12. Transmission Line Mutual Induction -- Ch. 13. Pilot Protection Systems -- Ch. 14. Complex Transmission Protection -- Ch. 15. Series-Compensated Line Protection -- pt. IV. Apparatus Protection -- Ch. 16. Bus Protection -- Ch. 17. Transformer and Reactor Protection -- Ch. 18. Generator Protection -- Ch. 19. Motor Protection -- pt. V. System Aspects of Protection -- Ch. 20. Protection Against Abnormal System Frequency -- Ch. 21. Protective Schemes for Stability Enhancement -- Ch. 22. HVDC Protection -- Ch. 23. SSR Protection -- pt. VI. Reliability of Protective Systems -- Ch. 24. Basic Reliability Concepts -- Ch. 25. Reliability Analysis -- Ch. 26. Reliability Concepts in System Protection -- Ch. 27. Fault Tree Analysis of Protective Systems -- Ch. 28. Markov Modeling of Protective Systems. App. A. Protection Terminology -- App. B. Protective Device Classification -- App. C. Overhead Line Impedances -- App. D. Transformer Data -- App. E. 500 kV Transmission Line Data.
Includes bibliographical references and index.
1
Keywords: Electric power systems -- Protection